Evaluation of Light-curing Intensity Output and Students’ Knowledge among Dental Schools in Riyadh City - Binalrimal, Sultan; Alamry, Sarah; Alenezi, Mona; Alfassam, Nora; Almuammar, Sara (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The aim of this study is interpreting the dental student’s knowledge of light-curing units from different universities and colleges in Riyadh city and to evaluate the intensity of the light output of light-emitting diode (LED)-curing devices in dental school clinics in Riyadh, Saudi Arabia. METHODS: One hundred eighty-two visible light-curing (VLC) units were randomly selected to have their light intensity output evaluated using Demetron® L.E.D. Radiometer – Kerr among dental school clinics in Riyadh city. The university hospitals we visited are King Khalid University Hospital, King Saud bin Abdulaziz University Hospital, Dar Al Uloom University Hospital, Alfarabi colleges’ dental clinics, and Princess Nourah Bint Abdulrahman University Hospital. To evaluate the knowledge of dental students about light intensity output, a questionnaire was given to the students. RESULTS: Out of the VLC units, 22 units (12%) measured inadequate intensity, 91 units (50%) measured marginal intensity, and 69 (37%) measured adequate intensity. The statistical significance was up to p < 0.05, p = 0. Most students and interns did not think that light-curing unit intensity influenced the tooth pulp (55.8%) and also reported not know the minimum wavelength of light cure intensity (62%). CONCLUSION: A significant difference was found between the light cure intensities in universities. As for the students’ knowledge, the research revealed poor insight toward basic concepts of VLC units and its maintenance.